2009
DOI: 10.4161/pri.3.1.8601
|View full text |Cite
|
Sign up to set email alerts
|

Metal binding sheds light on mechanisms of amyloid assembly

Abstract: β-2 microglobulin (β2m) is the protein responsible for amyloid deposition in Dialysis-Related Amyloidosis (DRA). Aggregation can be induced by various solution conditions including exposure to divalent metal, incubation at acidic pH, and limited proteolysis. Using Cu 2+ as a trigger, we have trapped, isolated, and crystallized a stable oligomer of β2m that is populated under amyloidogenic solution conditions (Calabrese et al. Nat Struct Mol Biol 2008; 15:965-71). This structure reveals that Cu 2+ -binding is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
44
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 44 publications
3
44
0
Order By: Relevance
“…Such changes in the intermolecular interactions of the late aggregates, observed for other fibrillar aggregates, 26 might be used to support the hypothesis stating that the late aggregates form fibrillar structures.…”
Section: Biochemistrysupporting
confidence: 58%
See 1 more Smart Citation
“…Such changes in the intermolecular interactions of the late aggregates, observed for other fibrillar aggregates, 26 might be used to support the hypothesis stating that the late aggregates form fibrillar structures.…”
Section: Biochemistrysupporting
confidence: 58%
“…Such distinct biochemical features might indicate different aggregate forms representing different stages of the aggregation process. 26 The kinetic analysis revealed that aggregation was much faster at 50 μM zinc than it was at 10 μM zinc (Figure 4 and Figure S3 of the Supporting Information), suggesting that using a fixed incubation time, the aggregates formed at low zinc supplies would represent the early stages of the process while those formed at high zinc would represent the late stages. In this respect, we considered the aggregates formed in 2 h at low zinc concentrations (≤10 μM) as the early aggregates and those formed at high concentrations (≥50 μM) as the late aggregates.…”
Section: Biochemistrymentioning
confidence: 98%
“…or Zn 2? (Calabrese and Miranker 2009), binding to the extracellular matrix or that polymerization of Ab might depend on lysine cross-linking (Boros et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Other aspects of the dialysis treatment also play a role in the converting soluble monomeric β2m into insoluble fibrils, but the exact causes are still subject to debate. Research has shown that acidic conditions, 8,9 certain mutations, 10,11 cleavage of the six N-terminal amino acids, 12,13 limited proteolysis, 14 stoichiometric concentrations of Cu(II), 1520 and other conditions 21,22 can induce the β2m amyloidosis in vitro. 8,23 Our group has been interested in the potential role that Cu(II) could play in inducing the β2m amyloid formation.…”
mentioning
confidence: 99%
“…20,27 The oligomers, particularly the dimer 28,29 and tetramer 29,30 maintain a native-like structure. 27,29,31,32 Cu(II) has also been shown to play a catalytic role in the formation of β2m fibrils as it is necessary for oligomer formation but is released before the final fibrils are formed.…”
mentioning
confidence: 99%